Effect of complementary foods fortified with Moringa oleifera leaf powder on hemoglobin concentration and growth of infants in the Eastern Region of Ghana. Issue 1 (20th November 2018) - Boateng, Laurene; Quarpong, Wilhemina; Ohemeng, Agartha; Asante, Matilda; Steiner‐Asiedu, Matilda
Abstract: Complementary foods that are deficient in both macronutrients and micronutrients coupled with a high burden of infections during the complementary feeding period are major underlying causes of child malnutrition in developing countries. Among the recent efforts to combat malnutrition by improving the quality of complementary foods in the developing world is the use of Moringa oleifera leaf powder (MLP) as a food fortificant. We conducted a randomized controlled trial to test the effect of feeding MLP‐fortified complementary food on hemoglobin concentration and growth of infants and young children after 4 months of feeding. Infants aged 8–12 months were randomly assigned to receive one of three study foods; Weanimix a cereal‐legume blend formulated with Moringa ( MCL‐35g ), MLP sprinkled on infants' usual complementary foods ( MS‐5g ) and the control food Weanimix without Moringa ( CF‐35g ). Blood samples for hemoglobin determination as well as dietary intake and anthropometric data were collected at baseline and endline for 237 infants who completed the study. Data analysis was performed with SPSS (version 20) and comparisons were done by analysis of covariance (ANCOVA). There were no significant differences in hemoglobin concentration or growth indicators at endline between the three study groups. Findings of this study indicated that feeding infants a 5 g daily dose of MLP, either as part of a cereal‐legume blend or as a supplement which was sprinkled on infants' usual complementary foods for 4 months, did not significantly improve infants' hemoglobin concentration or growth indicators. Abstract : Feeding infants with complementary foods fortified with a daily dose of 5 g of Moringa oleifera Leaf Powder did not significantly improve either their hemoglobin concentrations or growth indicators after 4 months of feeding.